Pengaruh Kualitas Pelayanan, Kepercayaan dan Kepuasan terhadap Loyalitas Nasabah PT Bank Syariah Mandiri Kendari - Indri Hapsari; Murini Murini (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2022)
BSM Customers in Kendari Branch searched, select and use the entire services of a bank if the quality of the bank's services is able to meet the customer's needs. However, this is not enough for customers if the value of the benefits of banking products offered is not in accordance with the perception of the applicable customer value. In this case the better the quality of service, trust and customer satisfaction, the higher the customer's loyalty at PT Bank Syariah Mandiri Kendari Branch. The purpose of this study is to analyze and determine the influence of service quality, trust and customer satisfaction with customer loyalty at PT Bank Syariah Mandiri Kendari Branch. The method used in this study is in the form of primary data and secondary data that are qualitative and quantitative using multiple linear regression analysis software with the help of SPSS 16. The results show that simultaneously (together) between service quality, trust and customer satisfaction there is an influence Against customer loyalty at PT Bank Syariah Mandiri Kendari Branch while partially that the quality of service, trust and customer satisfaction there is an influence on customer loyalty at PT Bank Syariah Mandiri Kendari Branch